2014
DOI: 10.1007/s10943-014-9849-8
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Religiosity and Internet Pornography Use

Abstract: Internet pornography (IP) consumption has increased, resulting in functioning and psychological problems. Thus, understanding what variables affect IP uses is needed. One of the variables may be religion. College students (N = 223) completed questions on IP use and religion. About 64 % ever viewed IP and 26 % currently viewed IP, at a rate of 74 min per week. IP use interfered with their relationship with God and spirituality. Religious individuals were less likely to ever or currently view IP. Intrinsic and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 34 publications
4
41
0
2
Order By: Relevance
“…Armfield and Holbert (2003) investigated the relationship between piety and Internet use in their study, finding that religious belief is a relatively weak predictor of Internet use compared to variables such as age, income, and education. Short, Kasper, and Wetterneck (2015) aimed to investigate the relationship between religious beliefs and Internet use intended for pornography in their study and found a negative correlation between the frequency of Internet use intended for pornography and piety. In situations where individuals comply with their religious beliefs and spiritual values, the level of Internet use intended for pornography is near zero.…”
Section: Discussionmentioning
confidence: 99%
“…Armfield and Holbert (2003) investigated the relationship between piety and Internet use in their study, finding that religious belief is a relatively weak predictor of Internet use compared to variables such as age, income, and education. Short, Kasper, and Wetterneck (2015) aimed to investigate the relationship between religious beliefs and Internet use intended for pornography in their study and found a negative correlation between the frequency of Internet use intended for pornography and piety. In situations where individuals comply with their religious beliefs and spiritual values, the level of Internet use intended for pornography is near zero.…”
Section: Discussionmentioning
confidence: 99%
“…(Patterson & Price, 2012; see also Grubbs et al, 2015b;Nelson et al, 2010;Perry, 2017b;Short et al, 2015) that can have relational consequences (Doran & Price, 2014;Perry, 2016, Perry & Snawder, 2017. Several other data limitations are worth addressing in order to chart a path for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Household income was measured in categories from (1) less than $5,000 to (19) $200,000 or more. Religious factors are highly correlated with both pornography use (Perry, 2016;Perry & Hayward, 2017;Poulsen et al, 2013;Short, Kasper, & Wetterneck, 2015) and marital quality (Ellison et al, 2010;Mahoney, 2010;Perry, 2016). Thus, models included controls for religious commitment, tradition, and conservatism.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations